Exploiting Necroptosis for Therapy of Acute Lymphoblastic Leukemia - Mezzatesta, Caterina; Bornhauser, Beat C. (Frontiers in Cell and Developmental Biology, 2019)
Escape from chemotherapy-induced apoptosis is a hallmark of drug resistance in cancer. The recent identification of alternative programmed cell death pathways opens up for possibilities to circumvent the apoptotic blockade in drug resistant cancer and eliminate malignant cells. Indeed, we have recently shown that programmed necrosis, termed necroptosis, could be triggered to induce cell death in a subgroup of primary acute lymphoblastic leukemia (ALL) including highly refractory relapsed cases. In this review we focus on molecular mechanisms that drive drug resistance in acute lymphoblastic leukemia of childhood and discuss the potential of necroptosis activation to eradicate resistant disease.